THE CAUSE OF VISION ON THE THOUGHT OF IMAM IBN KATHIR DAMASCENE 774 H قضية الرؤية في فكر الإمام ابن كثير الدمشقي (ت: 774هـ) - Mohamed Mohamed Tolba Said (Jurnal Al-Hikmah: Jurnal Dakwah, 2018)
The subject of this research was The Vision of Allah on the Thought of Imam Ibn Kathir Damascene (774 H.). The objective of this research was to study The Vision of Allah on the thought of Imam Ibn Kathir through his books. The Research Methodology was using descriptive method. The resultsof this research were as follows; Imam Ibn Kathir had used provable method by Quran, Hadith, and Ijma`. Besides, he also used critical method when he had discussed with violators of his opinion, Imam Ibn Kathir followed Mazhab Ahl Alsunnah wal Jama’h in believing that the believers will see Allah with one’s own eyes in the Hereafter but he was against al-Mu’tazilah. [Pokok penelitian ini adalah Visi terhadap Allah dalam Pemikiran Imam Ibn Kathir Damaskus (774 H). Tujuan penelitian ini adalah untuk mempelajari Visi terhadap Allah dalam pemikiran Imam Ibnu Katsir melalui buku-bukunya. Metodologi Penelitiannya menggunakan metode deskriptif. Hasil penelitian ini adalah sebagai berikut; Imam Ibnu Katsir telah menggunakan metode yang bisa dibuktikan oleh al-Quran, al-Hadits, dan Ijma`. Selain itu, ia juga menggunakan metode kritis ketika ia berdiskusi dengan para penentang pendapatnya, Imam Ibn Kathir mengikuti Mazhab Ahl Al -Sunnah wal Jama'h dengan meyakini bahwa orang-orang beriman akan melihat Allah dengan mata kepala sendiri di akhirat, tetapi ia menentang al-Mu 'tazilah]. Keywords: The Vision of Allah, Ibn Kathir Damascene, Ahl al-sunnah wal Jama’h.